1989
DOI: 10.1136/oem.46.7.473
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergy in an entomological research centre. I. Clinical aspects of reactions to the sheep blowfly Lucilia cuprina.

Abstract: Twenty eight per cent (15) of 53 workers engaged in a sheep blowfly breeding programme designed to control genetically the pest Lucilia cuprina experienced allergic manifestations resulting from contact with this insect. The most common symptoms were rhinitis, affected eyes, rashes, and lower respiratory symptoms, usually, but not always, immediate in type. A personal history of noninsect related asthma, allergic rhinitis, or eczema, or a combination of these was more common in the fly allergic group but some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…A number of entomologists either transferred to other areas to minimise contact with the allergens (Frankland, 1953;Harris-Roberts et al, 2011;Kaufman et al, 1986;Lunn and Hughes, 1967;Solley and Hyatt, 1980;Tee et al, 1985), or terminated their employment (Kaufman et al, 1989;Monk, 1988;Stevenson and Mathews, 1967). In one case (Stevenson and Mathews,, 1967) this was not sufficient to resolve his symptoms, as it was revealed he had worn his dirty work clothes home with him, and later he tested positive to dust from the rugs, mattress and stuffed furniture within his home, indicating that he had brought the allergens home on his clothing (Stevenson and Mathews, 1967).…”
Section: Occupational Management Of Adverse Work-related Health Outcomesmentioning
confidence: 89%
See 2 more Smart Citations
“…A number of entomologists either transferred to other areas to minimise contact with the allergens (Frankland, 1953;Harris-Roberts et al, 2011;Kaufman et al, 1986;Lunn and Hughes, 1967;Solley and Hyatt, 1980;Tee et al, 1985), or terminated their employment (Kaufman et al, 1989;Monk, 1988;Stevenson and Mathews, 1967). In one case (Stevenson and Mathews,, 1967) this was not sufficient to resolve his symptoms, as it was revealed he had worn his dirty work clothes home with him, and later he tested positive to dust from the rugs, mattress and stuffed furniture within his home, indicating that he had brought the allergens home on his clothing (Stevenson and Mathews, 1967).…”
Section: Occupational Management Of Adverse Work-related Health Outcomesmentioning
confidence: 89%
“…Wirtz (1980) reported in a cross-sectional survey that 27.8% of their respondents with allergic symptoms either left their job, or transferred to other areas, because of their symptoms. Kaufman et al (1989) reported in their cross-sectional study that asthma and chest tightness was either improved or eliminated by employing occupational hygiene measures. Furthermore, nine of the 12 workers who reported upper respiratory symptoms reported an elimination or significant reduction of symptoms a range of preventive measures, such as respirator use, local air extractor systems, wearing protective clothing, including a mask, and wet cleaning of cages and benches.…”
Section: Occupational Management Of Adverse Work-related Health Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…Die Sensibilisierung erfolgt per inhalationem und manifestiert sich als Rhinokonjunktivitis, Asthma bronchiale oder seltener perkutan mit der Folge einer Proteinkontakt urtikaria [17,18]. Berufsbedingte Sensibilisierungen gegenüber Insekten, verursacht durch Heuschrecken, Schmeißfliegen oder Kakerlaken sind wiederum v. a. bei im Labor exponierten Personen keine Seltenheit [2, 5,12,20,22]. Eine Untersuchung an Personen mit beruflichem Labortierkontakt von 1999-2000 in Groß britannien ermittelte eine Inzidenz berufsbedingter relevanter Inhalationsallergien durch die Arbeit mit Insekten im Labor für die Rhinitis mit 21/1000/Jahr und asthmatische Beschwerden mit 2,35/1000/Jahr, welche als hoch eingestuft wird [6].…”
Section: Berufsbedingte Inhalationsallergie Gegen Die Gemeine Hausfliunclassified
“…Thus occupational allergies to houseflies and blow flies are related to the degree of exposure to dust from cages or fly rooms [22,23], However, airborne fragments of fly bodies may prove equally allergenic since the opera tion of electrocuting fly traps in the laboratory tests cause an increase in respirable particle counts of up to 500 times the background level [24], In a similar reaction to the adult flies, reactions to fly larvae may also be related to peritrophic membrane extract. Those who breed maggots or use them as fishing bait may show asthma, rhinoconjunctival reactions or urticaria.…”
Section: Moths Locusts Flies and Beetles As Occupational And Enviromentioning
confidence: 99%